Perancangan Media Pembelajaran IPS Kelas 6 Di Sekolah Dasar Negeri 2 Rowobungkul Kabupaten Blora Berbasis Multimedia Interaktif - ., Suraji; Nugrohotomo, Gesang Kristianto (Seruni - Seminar Riset Unggulan Nasional Inoformatika dan Komputer, 2013)
ABSTRACT: Innovation and Technology development in education aspect and currently learning really indispensable at school especially for instructors in present duty assignment and more material complex. Media interactiving to constitute one of innovation in world current education, as one of learned source that can be utilized deep learning at schooled in particular for Social Science subject at SD Country 2 Rowobungkul. All this time trick forwarding Social Science study material is still utilize discourse method and writing at blackboard that insufficiently been accepted by participant is taught eventually participant educativing to have characteristic and learning ability that variably. Therefore designed by interactive learning media that is designed as effective as and one pulls maybe to be able to be utilized as media of alternative in learning at schooled. Because that interactive learning that gets multimedias basis is expected gets to help settle that problem. This research is executed to know media makings procedure Socials Science interactive learning divide class Elementary School 6 get multimedias basises and its following ones is expected to make easy deep teaching and learning activity processes at schooled. Of this research result is expected gets to create effective learning media and efficient for trade material Social Science Subject at Indonesian about kegatan exports and import at Country Elementary School 02 Rowobungkul Bloras Regencies. Key word, Learning media, IPS, Multimedia Interaktif ABSTRAK: Inovasi dan pengembangan Teknologi dalam aspek pendidikan dan pembelajaran saat ini memang sangat dibutuhkan di sekolah terutama bagi para pengajar dalam menyajikan tugas-tugas dan bahan yang lebih kompleks. Media interaktif merupakan salah satu inovasi dalam dunia pendidikan saat ini, sebagai salah satu sumber belajar yang dapat dimanfaatkan dalam pembelajaran di sekolah khususnya untuk mata pelajaran Ilmu Pengetahuan Sosial di SD Negeri 2 Rowobungkul. Selama ini cara penyampaian materi pelajaran Ilmu Pengetahuan Sosial masih menggunakan metode ceramah dan menulis dipapan tulis yang kurang diterima oleh peserta didik padahal peserta didik memiliki karakteristik dan kemampuan belajar yang berbeda-beda. Maka dirancang media pembelajaran interaktif yang didesain seefektif dan semenarik mungkin agar dapat digunakan sebagai media alternatif dalam pembelajaran di sekolah. oleh sebab itu pembelajaran interaktif yang berbasis multimedia diharapkan dapat membantu mengatasi masalah tersebut. Penelitian ini dilaksanakan untuk mengetahui prosedur pembuatan media pembelajaran interaktif Ilmu Pengetahuan Sosial bagi Sekolah Dasar kelas 6 berbasis multimedia dan yang nantinya diharapkan untuk memudahkan dalam proses kegiatan belajar mengajar di sekolah. Dari hasil penelitian ini diharapkan dapat menciptakan media pembelajaran yang efektif dan efisien untuk Mata Pelajaran Ilmu Pengetahuan Sosial materi Perdagangan di Indonesia tentang kegatan ekspor dan impor di Sekolah Dasar Negeri 02 Rowobungkul Kabupaten Blora. Kata kunci, Media pembelajaran, IPS, Multimedia Interaktif